2006
DOI: 10.1111/j.1471-8286.2005.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA markers for Plasmopara viticola, the causal agent of downy mildew of grapes

Abstract: Microsatellite loci were isolated from Plasmopara viticola (Oomycetes), the causal agent of downy mildew of grape, one of the most damaging fungal diseases of grapevine worldwide. Seven polymorphic loci were obtained from an enriched partial genomic library. A low genetic diversity was observed at all loci, with a mean observed allele number of 3.75 and an observed heterozygosity ranging from 0.074 to 0.547. Cross‐amplification tests on three closely related taxa indicated that two loci could be used in other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 4 publications
0
54
1
Order By: Relevance
“…An example of contrasted mating systems in two closely related species is given by Plasmopara viticola and P. halstedii, oomycetes responsible respectively for the downy mildews of grapevine and sunflower. Molecular markers showed that the two species displayed similar levels of genetic diversity (Chen et al, 2007;Delmotte et al, 2006). The homothallic species P. halstedii showed considerable heterozygote deficit (F IS = 0.95), probably due to limited dispersal ability before mating and thus lack of available sexual partners in the field (Giresse et al, 2007), while the populations of P. viticola only slightly deviated from HardyWeinberg proportions (Chen et al, 2007;Delmotte et al, 2006).…”
Section: Mating Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…An example of contrasted mating systems in two closely related species is given by Plasmopara viticola and P. halstedii, oomycetes responsible respectively for the downy mildews of grapevine and sunflower. Molecular markers showed that the two species displayed similar levels of genetic diversity (Chen et al, 2007;Delmotte et al, 2006). The homothallic species P. halstedii showed considerable heterozygote deficit (F IS = 0.95), probably due to limited dispersal ability before mating and thus lack of available sexual partners in the field (Giresse et al, 2007), while the populations of P. viticola only slightly deviated from HardyWeinberg proportions (Chen et al, 2007;Delmotte et al, 2006).…”
Section: Mating Systemsmentioning
confidence: 98%
“…Molecular markers showed that the two species displayed similar levels of genetic diversity (Chen et al, 2007;Delmotte et al, 2006). The homothallic species P. halstedii showed considerable heterozygote deficit (F IS = 0.95), probably due to limited dispersal ability before mating and thus lack of available sexual partners in the field (Giresse et al, 2007), while the populations of P. viticola only slightly deviated from HardyWeinberg proportions (Chen et al, 2007;Delmotte et al, 2006). Fungi exhibit a variety of other ways to recombine genetic information than sexuality, gathered under the terms of parasexuality or somatic recombination (Bos, 1996).…”
Section: Mating Systemsmentioning
confidence: 99%
“…These markers allow high-throughput genotyping of isolates through extraction of DNA directly from plant lesions, avoiding time-consuming subculture of isolates on leaves. To date, 11 microsatellites and eight SNP markers have been described in P. viticola (5,6,8). Related to the economic importance of this pathogen species, the low number of genetic markers available in P. viticola reflects the difficulties that were previously encountered by research groups to isolate microsatellites using traditional methods (5,7,8).…”
mentioning
confidence: 99%
“…We extracted the DNA from P. viticola isolates using freezedried infected plant tissue as previously described by Delmotte et al (3). All PCR amplification reactions were carried out in a final volume of 25 l, containing 10 ng of genomic DNA, 2 mM MgCl 2 , 150 M each deoxynucleoside triphosphate (dNTP), 4 pmol of each primer, and 0.2U Taq Silverstar DNA polymerase (Eurogentec) in reaction buffer.…”
mentioning
confidence: 99%
“…The species specificity of the marker is especially important, as it allows high-throughput genotyping of isolates directly from sporulating lesions collected from host leaves, avoiding the need for labor-intensive isolate subculture. Eleven microsatellite markers are available to assess the genetic structure within populations of P. viticola (3,9). Among the 11 markers developed, 3 of them were difficult to score and the remaining 8 markers had a low number of alleles (mean number of alleles/locus of 3.7 Ϯ 1.1).…”
mentioning
confidence: 99%